2016
DOI: 10.1186/s12940-016-0180-6
|View full text |Cite
|
Sign up to set email alerts
|

Aneuploidy: a common and early evidence-based biomarker for carcinogens and reproductive toxicants

Abstract: Aneuploidy, defined as structural and numerical aberrations of chromosomes, continues to draw attention as an informative effect biomarker for carcinogens and male reproductive toxicants. It has been well documented that aneuploidy is a hallmark of cancer. Aneuploidies in oocytes and spermatozoa contribute to infertility, pregnancy loss and a number of congenital abnormalities, and sperm aneuploidy is associated with testicular cancer. It is striking that several carcinogens induce aneuploidy in somatic cells,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 139 publications
(130 reference statements)
0
16
0
Order By: Relevance
“…Multiple studies have demonstrated an association between environmental factors and increased sperm aneuploidy frequencies. Associations that have been reported include smoking, air pollution, benzene, chemotherapy, parabens, polychlorinated biphenyl and scrotal heating, amongst others (Robbins et al 2005, Tempest et al 2005, Perry 2008, Xing et al 2010, Ji et al 2012, Mcauliffe et al 2012, Figueroa et al 2015, Governini et al 2015, Radwan et al 2016, Perry et al 2016, Beal et al 2017, Jurewicz et al 2017, Rives et al 2017. It is important to note that such studies in humans are notoriously difficult to design, compare and reproduce, and it is extremely difficult to prove causation given the multitude of confounding factors that exist in such studies.…”
Section: Sperm Aneuploidy As a Biomarker To Monitor Environmental Andmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies have demonstrated an association between environmental factors and increased sperm aneuploidy frequencies. Associations that have been reported include smoking, air pollution, benzene, chemotherapy, parabens, polychlorinated biphenyl and scrotal heating, amongst others (Robbins et al 2005, Tempest et al 2005, Perry 2008, Xing et al 2010, Ji et al 2012, Mcauliffe et al 2012, Figueroa et al 2015, Governini et al 2015, Radwan et al 2016, Perry et al 2016, Beal et al 2017, Jurewicz et al 2017, Rives et al 2017. It is important to note that such studies in humans are notoriously difficult to design, compare and reproduce, and it is extremely difficult to prove causation given the multitude of confounding factors that exist in such studies.…”
Section: Sperm Aneuploidy As a Biomarker To Monitor Environmental Andmentioning
confidence: 99%
“…Genotoxic and mutagenic studies frequently assess chromosome aberrations in somatic cells to determine whether compounds have carcinogenic potential through multiple techniques, including FISH, comet assay and the micronucleus assay, amongst others. Inclusion of sperm aneuploidy in such studies could also provide valuable information on reproductive toxicants and will ultimately provide a more comprehensive evaluation of carcinogenicity and reproductive toxicity (Mandrioli et al 2016). In addition to investigating chromosome aneuploidy in sperm, other biomarkers should be considered to monitor exposure to environmental hazards, including sperm DNA integrity (DNA fragmentation), chromatin modifications (epigenetics) and nuclear organization amongst others (Anton & Krawetz 2012).…”
Section: Sperm Aneuploidy As a Biomarker To Monitor Environmental Andmentioning
confidence: 99%
“…The comparable effect of EDs is known during spermatogenesis: BPA is capable of affecting meiotic division and chromosome segregation, increasing the incidence of aneuploidy-derived disorders [73]. In addition, the molecular mechanism of BPA consists in impacting several signal pathways and results in the change of protein kinase A activity and protein tyrosine phosphorylation, ATP generation, and oxidative stress-related enzymes (i.e., peroxiredoxin-5, glutathione peroxidase 4, succinate dehydrogenase), crucial for sperm motility and ability of oocyte fertilization [26,27,74].…”
Section: Molecular Mechanism Of Eds In Extremely Low Dosesmentioning
confidence: 96%
“…Recently, aneuploid embryos have been discovered to account for >50% of early miscarriages (7,8). Aneuploidy, defined as structural and numeric aberrations of chromosomes, is prevalent in human embryonic development (9). It is considered to be a primary genetic origin of implantation failure, miscarriage, and congenital abnormalities, both naturally and after IVF (9)(10)(11)(12).…”
mentioning
confidence: 99%
“…Aneuploidy, defined as structural and numeric aberrations of chromosomes, is prevalent in human embryonic development (9). It is considered to be a primary genetic origin of implantation failure, miscarriage, and congenital abnormalities, both naturally and after IVF (9)(10)(11)(12). Despite extensive investigation, little is known about the complex origins and mechanisms underlying aneuploidy.…”
mentioning
confidence: 99%